2023
DOI: 10.1038/s41698-023-00424-6
|View full text |Cite
|
Sign up to set email alerts
|

An international multi-institutional validation study of the algorithm for prostate cancer detection and Gleason grading

Abstract: Pathologic examination of prostate biopsies is time consuming due to the large number of slides per case. In this retrospective study, we validate a deep learning-based classifier for prostate cancer (PCA) detection and Gleason grading (AI tool) in biopsy samples. Five external cohorts of patients with multifocal prostate biopsy were analyzed from high-volume pathology institutes. A total of 5922 H&E sections representing 7473 biopsy cores from 423 patient cases (digitized using three scanners) were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“… 21 detection of prostate cancer and perineural invasion and automated Gleason grading CNN, supervised learning biopsy training: 549 slides external ‡ : 100 consecutive cases, 1,627 slides detection: AUC 0.991 GS 6 or ASAP vs. GS 7–10: AUC 0.941 GP3–4 or ASAP vs. GP5: AUC 0.971 perineural invasion: AUC 0.957 Tolkach et al. 22 detection and automated GG grading CNN, supervised learning RP training: TCGA-PRAD dataset external 1 22 : 2 cohorts (592 and 279 patients) external 2 36 : 7473 cores, 423 patients from five centers external 1: detection: AUC 0.9919 and 0.9918 GG grading † : κ 0.51–0.66 external 2: detection: sensitivity 0.971–1.000; specificity 0.875–0.976 grading: κ quad 0.72–0.77 Ström et al. 37 detection, measurement of tumor length and automated grading DNN, supervised learning biopsy training: 1,069 patients, 6,953 slides external: Imagebase and Karolinska dataset (330 cores from 73 cases) detection: AUC 0.986 GG grading: for Imagebase dataset, mean pairwise κ 0.62.…”
Section: Development Of Ai Models For Prostate Cancer Managementmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 detection of prostate cancer and perineural invasion and automated Gleason grading CNN, supervised learning biopsy training: 549 slides external ‡ : 100 consecutive cases, 1,627 slides detection: AUC 0.991 GS 6 or ASAP vs. GS 7–10: AUC 0.941 GP3–4 or ASAP vs. GP5: AUC 0.971 perineural invasion: AUC 0.957 Tolkach et al. 22 detection and automated GG grading CNN, supervised learning RP training: TCGA-PRAD dataset external 1 22 : 2 cohorts (592 and 279 patients) external 2 36 : 7473 cores, 423 patients from five centers external 1: detection: AUC 0.9919 and 0.9918 GG grading † : κ 0.51–0.66 external 2: detection: sensitivity 0.971–1.000; specificity 0.875–0.976 grading: κ quad 0.72–0.77 Ström et al. 37 detection, measurement of tumor length and automated grading DNN, supervised learning biopsy training: 1,069 patients, 6,953 slides external: Imagebase and Karolinska dataset (330 cores from 73 cases) detection: AUC 0.986 GG grading: for Imagebase dataset, mean pairwise κ 0.62.…”
Section: Development Of Ai Models For Prostate Cancer Managementmentioning
confidence: 99%
“…In Tolkach’s study, pathologists recognized false-positive alerts from AI as useful warnings, as these highlighted areas required additional attention and immunostaining for further evaluation. 36 However, there is a risk that pathologists may overly rely on AI predictions without critically evaluating its predictions. Meyer’s small-scale study showed that pathologists were willing to trust AI regardless of its accuracy.…”
Section: Challenges Of Application Of Ai In Clinicmentioning
confidence: 99%
“…HALO Prostate AI, developed by Indica Labs is a DL-based screening tool currently CE-marked under IVDD, and its validation study was published in August 2023. The model identified biopsies that contained tumors with sensitivity, specificity, and negative predictive values ranging from 0.971 to 1.000, 0.875 to 0.976, and 0.988 to 1.000, respectively, across multiple test cohorts [59]. Histotype Px, by DoMore Diagnostics (CE-marked under IVDD), uses deep learning to provide risk stratification for patients with CRC using WSI.…”
Section: Examples Of Ai Tools Approved For Clinical Use In the Usa An...mentioning
confidence: 99%
“…Artificial intelligence (AI) has the potential to be an accurate and time efficient technology that can aid pathologists in diagnosing muscularis propria invasion. AI has already shown promising results in several areas of pathology, such as Gleason grading for prostate adenocarcinoma, 7 11 melanoma scoring, 12 and more. In previous studies we have developed and applied a new algorithmic approach called hierarchical contextual analysis (HCA) for the detection of perineural invasion in pancreatic adenocarcinoma, 13 and also for the detection of ganglion cells, a process of significant importance for improving the accuracy of Hirschsprung's disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%